2019
DOI: 10.1002/acm2.12571
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric effect of body contour changes for prostate and head and neck volumetric modulated arc therapy plans

Abstract: Body contour changes are commonly seen in prostate and head and neck (H&N) patients undergoing volumetric modulated arc therapy (VMAT) treatments, which may cause a discrepancy between the planned dose and the delivered dose. Dosimetrists, radiation oncologists or medical physicists sometimes are required to visually assess the dosimetric impact of body contour changes and make a judgment call on whether further re‐assessment of the plan is needed. However, an intuitive judgment cannot always be made in a time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Secondly, it was found that the effective separation change diameter exceeds 1 cm for patients where the GDSA µ exceeds 3%. Sun et al 20 found that uniform body changes less than 1 cm were unlikely to warrant further assessment due to changes in delivered dose. Similarly, Chen et al 21 found that the dose delivered to the PTV significantly increased by 2%-3% for a 2-5 mm change in body contour.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, it was found that the effective separation change diameter exceeds 1 cm for patients where the GDSA µ exceeds 3%. Sun et al 20 found that uniform body changes less than 1 cm were unlikely to warrant further assessment due to changes in delivered dose. Similarly, Chen et al 21 found that the dose delivered to the PTV significantly increased by 2%-3% for a 2-5 mm change in body contour.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, it was found that the effective separation change diameter exceeds 1 cm for patients where the GDSA µ exceeds 3%. Sun et al 20 . found that uniform body changes less than 1 cm were unlikely to warrant further assessment due to changes in delivered dose.…”
Section: Discussionmentioning
confidence: 99%
“…This means that for these patients anatomical changes were taken into account to some extent. Sun et al studied the effect of body contour changes on the position of isodose lines for prostate VMAT [27]. They found that the 95% isodose line shifts by less than 1 mm in case of a body contour change of 1 cm in all directions but posterior, which shows that the effect of these kind of anatomical changes is quite small.…”
Section: Discussionmentioning
confidence: 99%
“…8 External changes greater than 1 cm can shift the 95% and 93% isodose lines up to 4 mm. 10 This impact on delivered dose can result in unintended overdosage to nearby organs, associated with worsened toxicity, or underdosage to tumour sites, associated with decreased local control. 8 Anatomical changes are observed daily throughout RT via cone-beam computed tomography (CBCT) scans.…”
Section: Introductionmentioning
confidence: 99%
“…These changes can be due to a combination of weight loss, dehydration, tumour shrinkage, inflammation, muscle atrophy or radiation impacts on normal tissue 8 . External changes greater than 1 cm can shift the 95% and 93% isodose lines up to 4 mm 10 . This impact on delivered dose can result in unintended overdosage to nearby organs, associated with worsened toxicity, or underdosage to tumour sites, associated with decreased local control 8 …”
Section: Introductionmentioning
confidence: 99%